Companion Problematics: Abu Rayyah’s Critical Study of Abu Hurairah and His Role in Hadith Understanding - Ruston Nawawi (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2024)
This article aims to analyse Abu Rayyah’s criticism of Abu Hurairah in the context of understanding the hadith. The discussion of the narrators of the Prophet’s hadith has invited long-standing problems among hadith researchers ranging from friends to hadith recorders, which cannot be separated from this study. The negative aspect causes the Prophet’s hadith to be faced with doubt about its truth and opens up opportunities for those who have bad intentions towards Islam in general, especially towards the Prophet’s hadith. This article was reviewed using a literature study. Data collection techniques were conducted through identification, classification, and critical analysis of the hadith text, sanad, and matan. The analysis is done with a descriptive-analytical approach. This article concludes that the Prophet’s hadith polemics towards the matan and the sanad, which are made up of the narrators of the hadith themselves. The harshest accusations were directed at the Prophet’s companions, especially at the person of Abu Hurairah and his role in narrating the hadith of the Prophet. Mahmud Abu Rayyah said that in Abu Hurairah’s history, there were lies because he had memorised many hadiths. Indirectly, this accusation essentially casts doubt on the authenticity of Abu Hurairah in particular and in general to all of the Prophet’s companions. In the study of hadith science, all of the Prophet’s companions must have a just nature.